FOSTERING LOCAL TALENT THROUGH INNOVATION AND COLLABORATION IN INDONESIA’S CREATIVE ECONOMY - Adelia Azzahra (Publikasi Indonesia, 2023)
This study aims to explore the role of innovation and collaboration in the development of local talent in Indonesia's creative economy sector. Despite significant growth in this sector, challenges related to access to resources, networks, and infrastructure still hinder the full potential of creative talent, especially in rural areas. Using a qualitative approach, the research gathers data through semi-structured interviews with 20-30 industry stakeholders, including artists, designers, filmmakers, and related parties such as businesses, government officials, and educational institutions. The findings indicate that innovation in products and business models plays a critical role in helping local talent access new markets and differentiate themselves. Collaboration within the creative community and with the business and government sectors provides access to resources and networks that accelerate skill development. However, significant barriers, such as limited capital, poor infrastructure, and a lack of formal collaboration platforms, hinder this potential. Several strategies, such as utilizing crowdfunding, partnerships with investors, and forming informal industry networks, are identified as solutions to address these challenges. This study suggests that the growth of Indonesia's creative economy should be accelerated. There is a need for policies that support more structured collaboration and innovation and improved access to technology and resources for creative talent in underdeveloped areas.